2021
DOI: 10.17275/per.21.79.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Views of Social Studies Teachers on Scientific Research Methodology

Abstract: Scientific method is one means by which knowledge is created. The goal of the social studies course is to teach the methodology used by these sciences in accessing the subject information along with the information they provide from social sciences. Therefore, social studies teachers should be aware of the scientific research methodology so that they can teach according to this purpose. In this study, the focus was on how teachers consider scientific research. This study aimed to investigate social studies tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Science teachers generally have naïve and eclectic views of the SI aspects in Turkey (Cigdemoglu & Koseoglu, 2019;Mesci & Erdas-Kartal, 2021). Social science teachers' understanding of SI was similar to science teachers (Bayram, 2021). Research demonstrates that neither science nor social science teachers in Turkey hold informed views of SI.…”
Section: Cognitive Domains Of Inquiry Require Different Perspectives ...mentioning
confidence: 82%
“…Science teachers generally have naïve and eclectic views of the SI aspects in Turkey (Cigdemoglu & Koseoglu, 2019;Mesci & Erdas-Kartal, 2021). Social science teachers' understanding of SI was similar to science teachers (Bayram, 2021). Research demonstrates that neither science nor social science teachers in Turkey hold informed views of SI.…”
Section: Cognitive Domains Of Inquiry Require Different Perspectives ...mentioning
confidence: 82%
“…Por otra parte, se halló que la enseñanza de métodos de investigación en la educación superior presenta retos, como la delegación de la enseñanza a personas con diferentes niveles de experiencia y formación, la falta de cultura de aprendizaje y las limitaciones en la práctica profesional debido a deficiencias educativas y condiciones institucionales. A pesar de esto, se reconoce la importancia de los métodos de investigación en el desarrollo de la práctica profesional del profesorado, tal como lo han señalado autores destacados en el campo (Daniel, 2018;Bayram, 2021;Orellana-Fonseca et al, 2019).…”
Section: Fuente: Elaboración Propiaunclassified
“…Regarding the diagnostic evaluations of research methods instructors, Bayram's [41] study shows that students have false, incomplete, or mixed views about what research competencies are and what they are suitable for. One problem identified that restricts the development of research competencies is limited English proficiency.…”
Section: Undertaking Research With and Without The Development Of Res...mentioning
confidence: 99%
“…According to Nind's [2] study, the absence of this specific academic training in teaching methodologies translates into experiences that can be arduous for instructors. In this regard, the incompetence of instructors affects students' learning in serious ways [41]. This scenario can be understood from two points of view.…”
Section: Critical Engagements Through Pedagogical Practices Of Peer C...mentioning
confidence: 99%